Competitiveness and disclosure of intellectual capital: an empirical research in Portuguese banks - Cabrita, Rosário (2017)
Purpose – Thepurposeof thispaper is toinvestigatethe level of intellectual capital (IC) awarenessamong Portuguese bank managers and which disclosure techniques are most common. The annual report is regarded by some authors as the most important vehicle of information about banks’ affairs because of some specific characteristics of banks’ activities. However, organizations are increasingly using their webpages to disclose a broad spectrum of information. The objectives of this study are twofold: to investigate how Portuguese bank managers perceive the impact of IC disclosure on the bank’s competitiveness; and to assess the extent to which Portuguese banks voluntarily report their IC in annual reports vs webpages. Design/methodology/approach – The methodology involved in the exploratory study includes the collection of secondary data – annual reports and websites – collected from the 28 banks operating in Portugal, and semi-structured interviews from 25 banking managers. Content analysis is applied using a constructedindexbasedontwoEuropeanframeworks – IntellectusandInCaS– slightlymodifiedtotakeinto consideration the peculiarities of the sector. Findings – Results show higher level of IC disclosure in annual reports than that provided in websites. Human capital and structural capital are the most reported category in annual reports and, conversely, the disclosureofrelationalcapitalishigherinthewebpages.Findingsarefoundsimilarincomparisontovarious other studies on the subject which reveal very low level of IC disclosure, not yet receiving priority from the mentors of banks. Interviews reveal that not many managers recognize the need and significance of measuring and reporting IC, although it is recognized asa driver of competitiveness. For protecting business confidentiality, banks do not want to report information of sensitive nature. Researchlimitations/implications – Theanalysisislimitedtoasinglesector.Futureresearchcanexpand to other industries (e.g. manufacturing, technological, services) to enable a more comprehensive understanding of IC disclosure in Portugal. The cross-sectional approach is also a limitation. A longitudinal study could be conducted for capturing the trend of reporting practices during the period. Further research could apply researchmethodsother thancontentanalysis(e.g.questionnairesurvey,interviewsormixed-methods)inorder to obtain a more in-depth view of how the Portuguese organizations manage, measure and report their IC. Practical implications – Research may be of relevance for both banking managers and regulators. For banking managers because it offers an opportunity to envisage their banks’ future potential for growth and competitiveness. For regulators, the relevance of the study focusses on their understanding of developing mandatory reporting or additional policy requirements. This study provides a motivation for further research that contributes to a body of knowledge and practices on the IC disclosure. Social implications – Emerging from the years of a financial crisis, restoring trust and confidence is the most critical challenge for banks to become competitive. IC disclosure could help to restore confidence. Originality/value – The existing literature on the IC reporting and disclosure in the context of banking sector is limited. Based on the Intellectus model and the InCaS model we built an index of IC disclosure to banking sector which contributes to a greater accuracy, transparency and reliability in the disclosure of this unique sector. This initiative may encourage its applicability in other sectors.